Characterization of an alpha-macroglobulin-like glycoprotein isolated from the plasma of the soft tick Ornithodoros moubata - Kopácek, P; Weise, C; Saravanan, T; Vítová, K; Grubhoffer, L (European journal of biochemistry, 2000)
We report the identification of the first representative of the alpha-2-macroglobulin family identified in terrestrial invertebrates. An abundant acidic glycoprotein was isolated from the plasma of the soft tick Ornithodoros moubata. Its molecular mass is about 420 kDa in the native state, whereas in SDS/PAGE it migrates as one band of 190 kDa under nonreducing conditions and a band of 92 kDa when reduced. Chemical deglycosylation reveals that it is composed of two different subunits, designated A and B. The N-terminal amino-acid sequence of subunit A is similar to the N-terminus of invertebrate alpha-2-macroglobulin. Sequence analysis of several internal peptides confirms that the tick protein belongs to the alpha-2-macroglobulin family, and the protein is therefore referred to as tick alpha-macroglobulin (TAM). Functional analyses strengthen this assignment. TAM inhibits trypsin and thermolysin cleavage of the high-molecular-weight substrate azocoll in a manner similar to that of bovine alpha-2-macroglobulin. This effect is abolished by pre-treatment of TAM with methylamine. In the presence of TAM, trypsin is protected against active-site inhibition by soybean trypsin inhibitor. We cloned and sequenced a PCR product containing sequences from both subunits and spanning the N-terminus of subunit B and the putative 'bait region' (a segment of alpha-2-macroglobulin which serves as target for various proteases). This indicates that the two subunits are generated from a precursor polypeptide by post-translational processing.
Keywords: Molecular Sequence Data; Glycoproteins; Ticks; sekvence aminokyselin; inhibitory proteas; thermolysin; proteiny členovců; posttranslační úpravy proteinů; skot; Protease Inhibitors; Hemolymph; hemolymfa; trypsin; inhibitory trypsinu; Thermolysin; Trypsin; Protein Processing, Post-Translational; zvířata; Arthropod Proteins; Trypsin Inhibitors; Amino Acid Sequence; hmyzí proteiny; klíšťata; Cattle; alfa-makroglobuliny; molekulární sekvence - údaje; glykoproteiny; Sequence Analysis, Protein; sekvenční analýza proteinů; Insect Proteins; alpha-Macroglobulins; Animals